EFFECTIVENESS OF USED GOODS UTILIZATION AS LEARNING MEDIA ON FABLE FOR JUNIOR HIGH SCHOOL STUDENTS - Hindun Hindun; Fachrur Rajabani Ridwan (University of Kuningan, 2022)
The management of waste or used goods that is still not optimal causes various environmental problems. One way to reduce the presence of used goods is to recycle them into learning media. This study focuses on the effectiveness of used goods effectiveness as learning media on fable storytelling in class VII. The method used is descriptive-qualitative. Students’ storytelling skills were assessed by observation method using storytelling skills assessment rubric. Storytelling style, Mastery of the content of the story, volume of voice, and fluency were assessed. The results of the discussion show that the use of used goods as learning media is considered effective with an average student score of 89 which is included in the very good category.Keywords: used goods; learning media; storytelling skill; fable.